Pengaruh Ekstrak Buah Mengkudu (Morinda citrifolia) terhadap Waktu Kematian Cacing Ascaris suum, Goeze In Vitro - Deviana, Riza; Utari, Cr. Siti; Wasita, Brian (Nexus Biomedika, 2012)
Background: Mengkudu (Morinda citrifolia) has a terapeutic effect, such as antibacterial, anthelmintic and imunomodulator. This research was performed to understand the effect of Mengkudu (Morinda citrifolia) fruit extract on death time of Â Ascaris suum, Goeze In Vitro. Methods: This research was performed using experimental laboratory method with post-test only controlled group design. Adult Ascaris suum, Goeze (108 worms) were divided into 9 groups. The worms treated with NaCl 0.9 % solution and Piperazine 0.4% g/ml served as negative control and positive control group consecutively. The worms treated with increasing dose ofÂ  Mengkudu fruits (Morinda citrifolia) extract (1% g/ml, 2% g/ml, 4% g/ml, 6% g/ml, 8% g/ml, 10% g/ml, and 12% g/ml) served as treatment groups. Observations were performed every half hour until the worms died. LC50 and LT50 were calculated using probit analysis. Statistic analysis was performed using Kruskal-Wallis test continued by Post hoc Test with Bonferroni correction. Results: Probit analysis showed that LC50 and LT50 of Mengkudu fruits extract were 4.94% g/ml and 703.32 minutes. Kruskall-Wallis test showed that significance difference at least in the two groups. Post Hoc Mann-Whitney with Bonferroni correction test showed that treatment had significant difference (p < 0.001) to negative control and 12% g/ml group had significant difference to positive control group. Conclusions: Mengkudu (Morinda citrifolia) fruits extract can induce Ascaris suum death with the death time faster than standard medicine. Keywords: Mengkudu (Morinda citrifolia) extract, Ascaris suum, Piperazin.Â